Design of Web-Based Motorcycle Accessories Sales Information System at F4 Motor Store - Iriene Putri Mulyadi; Andri Swandi; Ferry Saputra; Rizal Bagus Achmad (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2025)
Abstract - The advancement of information technology currently has a significant impact on various aspects of human life, especially in the economic sector. One of the developments that greatly affects the world of economics is the implementation of E-Commerce. E-Commerce has become a strategic platform for companies, both large and small, to develop and expand their markets. Along with the rapid development of information technology, E-Commerce applications are expected to make it easier for people to purchase products without having to come directly to the store, as well as increase market reach and strengthen customer loyalty. F4 Motor Store, as one example, implements E-Commerce to provide convenience for customers and support more effective marketing strategies. The system design uses UML (Unified Modeling Language) which consists of use case diagrams, activity diagrams, sequence diagrams and class diagrams. then this system is developed using the SDLC (System Development Life Cycle) method with the PHP programming language, Adobe Dreamweaver CS3 text editor, and MySQL database. This application is also designed to present information related to products sold efficiently and accurately, providing a better shopping experience for users.Keywords: Design, Information System, Sales, F4 Motor Shop, Web Based Abstrak - Kemajuan teknologi informasi saat ini memberikan dampak yang cukup signifikan dalam berbagai aspek kehidupan manusia, terutama dalam bidang ekonomi. Salah satu perkembangan yang sangat mempengaruhi dunia ekonomi adalah penerapan E-Commerce. E-Commerce telah menjadi platform strategis bagi perusahaan-perusahaan, baik besar maupun kecil, untuk mengembangkan dan memperluas pasarnya. Seiring dengan perkembangan teknologi informasi yang semakin pesat, aplikasi E-Commerce diharapkan dapat memudahkan masyarakat dalam melakukan pembelian produk tanpa harus datang langsung ke toko, serta meningkatkan jangkauan pasar dan memperkuat loyalitas pelanggan. Toko F4 Motor sebagai salah satu contohnya, menerapkan E-Commerce untuk memberikan kemudahan bagi pelanggan dan mendukung strategi pemasaran yang lebih efektif. Perancangan sistem menggunakan UML (Unified Modelling Language) yang terdiri dari use case diagram, activity diagram, sequence diagram dan class diagram. kemudian sistem ini dikembangkan menggunakan metode SDLC (System Development Life Cycle) dengan bahasa pemrograman PHP, text editor Adobe Dreamweaver CS3, dan database MySQL. Aplikasi ini juga dirancang untuk menyajikan informasi terkait produk yang dijual secara efisien dan akurat, sehingga memberikan pengalaman berbelanja yang lebih baik bagi pengguna.Kata kunci: Perancangan, Sistem Informasi, Penjualan, Toko F4 Motor, Berbasis Web